Analysis of transfer length for prestressed FRP tendons in pretensioned concrete using composite beam theory. (15th January 2019) - Sha, Xin; Davidson, James S.
Abstract: This study developed a new method for determining the transfer length for FRP tendons in prestressed concrete. The governing equations are derived by combining the local bond-slip relationship for FRP tendons in concrete with composite beam theory. Comparisons to test data strain results demonstrate that the derived closed form solutions predict the transfer length of prestressed FRP tendons with good accuracy and efficiency. The developed method is then used to assess and discuss the difference between sequential release and simultaneous release of the tendons during manufacture of prestressed concrete members. Finally, based upon the developed theory, the key mechanical factors that influence the transfer length of FRP tendons are discussed.